100 kHz Narrow-Linewidth Burst-Mode MOPA Laser System With Uniform Envelope - Yu, Xin; Zhang, Shanchun; Peng, Jiangbo; Cao, Zhen; Gao, Long; Liu, Wenbei (Frontiers in Physics, 2022)
In this paper, a 100 kHz narrow-linewidth burst-mode laser system combined with master oscillator power amplifier (MOPA) structure was reported with stable pulse burst profile over 2 ms duration. A theoretical model was established to characterize and compensate the variation characteristics of coefficient of variation (COV) within burst envelope for double-pass three-stage amplification system, in terms of different parameters factors. Simulated results yielded similar tendency with the measured ones. For stable burst envelope with COV of 2.72% and 2.93%, output pulse energy at 100 kHz repetition rate was scaled up to 1.08 mJ and 4.38 mJ in that case of input average pulse energy of 8.6 nJ and 116.51 nJ, respectively. Corresponding Mx2 and My2 values with 2.2 and 2.4 were endowed with 1.08 mJ output single pulse energy, as well as 2.7 and 2.1 for 4.38 mJ pulse energy. Spectral linewidth of amplified pulses was measured to be less than 83.1 MHz and 67.9 MHz, with respect to output pulse duration of 10.3 ns and 96.1 ns respectively.